Resiliensi dan adaptasi petani garam akibat perubahan iklim di Desa Donggobolo, Kecamatan Woha, Kabupaten Bima - Davit Aldi; Nurhayati Nurhayati; Eka Intan Kumala Putri (Badan Kerjasama Pusat Studi Lingkungan (BKPSL) se-Indonesia bekerjasama dengan Pusat Penelitian Lingkungan Hidup IPB (PPLH-IPB), 2021)
Climate change possesses an impact on salt production and salt farmer households. The research was conducted in Donggobolo Village, Woha Sub-district, Bima in August-September 2020 by assessing the use of capital, resilience action and adaptation as a response of climate change. The results showed that physical capital is the main capital used by the public in the public and private sectors. The existence of facilities and village locations that can be accessed easily, make physical facilities easy to use in fulfilling a living. Self-organization action is an act of resilience with the highest value. Various adaptations are also carried out in accordance with the climatic phenomena faced, such as regulating the number of workers in salt ponds, stopping production, seeking alternative livelihoods and adapting technology. The number of salt farmers decreases during the long dry season with the possibility of stopping production due to the long dry season, which is not followed by the previous long rainy season causing the abundance of salt stocks and lower prices. Alternative income becomes a priority if the income during the salt season is not sufficient. The use of technology is still limited because most of them depend on the government.